Preliminary study of passive radiative cooling under Singapore's tropical climate - Han, Di (2022)
Sub-ambient cooling can be achieved through radiative coolers that selectively emit radiation within the atmospheric window (8–13 μm) to outer space and suppress absorption/emission of other wavelengths. This study explores the feasibility of adopting radiative cooling in the hot and humid climate of Singapore through both numerical and experimental approaches. A theoretical simulation based on the heat transfer balance is first proposed to obtain the cooling power of the radiative cooler considering different solar spectral irradiance and total water vapor column. The larger solar irradiance in Singapore, especially within the ultraviolet and visible light spectrum where the absorbance of the material is relatively high, could counteract its cooling effects. Moreover, the increased atmospheric radiation induced by higher humidity and temperatures in Singapore could worsen cooling performances of the radiative material. Next, experimental investigations were conducted by measuring the steady-state temperatures of two radiative coolers (photonic radiative cooler and enhanced specular reflector film) under three typical weather conditions in Singapore, namely clear, partly cloudy and cloudy skies. While both radiative coolers were unable to achieve daytime cooling performance on a clear day, the enhanced specular reflector (ESR) film with higher solar reflectance can reach sub-ambient temperatures on a cloudy day. When it comes to night-time, the steady-state temperature of the photonic radiative cooler and ESR film was about 3.5 °C and 5 °C lower than ambient, respectively.